2019
DOI: 10.1515/pp-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

CRS and HIPEC in patients with peritoneal metastasis secondary to colorectal cancer: The small-bowel PCI score as a predictor of survival

Abstract: BackgroundCombining cytoreductive surgery (CRS) with Hyperthermic IntraPeritoneal Chemotherapy (HIPEC) can benefit patients with peritoneal metastasis from colorectal cancer. The present study evaluates the small bowel subset of the Peritoneal Cancer Index (Small-Bowel-PCI score (SB-PCI), min-max 0–12) as a prognostic factor in such patients.MethodsWe retrospectively analyzed patients that underwent CRS and HIPEC for recurrent colorectal cancer with peritoneal metastasis. Patient characteristics, procedure det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…[ 5 7 ] This is especially important for small lesions that are difficult to detect by CT, conventional MRI, and PET-CT. [ 9 ] Patients detected with PMs might benefit from cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. [ 26 , 27 ] The present meta-analysis revealed that DWI had 89% pooled sensitivity (95% CI: 83%–93%) and 86% pooled specificity (95% CI: 79%–91%) for the diagnosis of PMs from various abdominal cancers.…”
Section: Discussionmentioning
confidence: 69%
“…[ 5 7 ] This is especially important for small lesions that are difficult to detect by CT, conventional MRI, and PET-CT. [ 9 ] Patients detected with PMs might benefit from cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. [ 26 , 27 ] The present meta-analysis revealed that DWI had 89% pooled sensitivity (95% CI: 83%–93%) and 86% pooled specificity (95% CI: 79%–91%) for the diagnosis of PMs from various abdominal cancers.…”
Section: Discussionmentioning
confidence: 69%
“…Small bowel engagement was the most common cause for openclose/debulking operations as patients with less than 2 m of small bowel left will have a poor quality of life together with short survival. An attempt to use the PCI score only for the small bowel for prognostic estimates have recently been made revealing the importance of the small bowel involvement [4].…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge on which patients should be operated on is still evolving. Patients with inoperable metastases in other organs than peritoneum [3], widespread disease on the small bowel [4] or physical poor performance [5] are generally not offered surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…There is a treatment that can be performed in patients with selective conditions at a high medical level and environment. Hyperthermic intraperitoneal chemotherapy (HIPEC) is performed simultaneously following cytoreductive surgery, which suppresses the progression of peritoneal metastasis [10] , [11] , [12] , [13] . However, this treatment is known to have a high risk of mortality.…”
Section: Introductionmentioning
confidence: 99%